2021
DOI: 10.11113/mjfas.v17n5.2356
|View full text |Cite
|
Sign up to set email alerts
|

Improved of Forecasting Sea Surface Temperature based on Hybrid ARIMA and Support Vector Machines Models

Abstract: Forecasting is a very effortful task owing to its features which simultaneously contain linear and nonlinear patterns. The Autoregressive Integrated Moving Average (ARIMA) model has been one the most widely utilized linear model in time series forecasting. Unfortunately, the ARIMA model cannot effortlessly handle nonlinear patterns alone. Thus, Support Vector Machine (SVM) model is introduced to solve nonlinear behavior in the datasets with high variance and uncertainty. The purposes of this study are twofold.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Various research has been done to predict and estimate the ocean surface temperature or SST to analyze thermal interchanges between oceans, atmosphere, behavior patterns of aquatic animals, and ocean or sea currents [7]. Ocean surface temperature has historically been estimated using linear regression and statistical approaches, such as the "Autoregressive Integrated Moving Average (ARIMA)" models [8], Machine learning techniques such as "support vector machines (SVMs)" have been employed in several types of research to predict SST [9] [10]. The "particle swarm optimization (PSO)" is also used for SST predictions in [11].…”
Section: Introductionmentioning
confidence: 99%
“…Various research has been done to predict and estimate the ocean surface temperature or SST to analyze thermal interchanges between oceans, atmosphere, behavior patterns of aquatic animals, and ocean or sea currents [7]. Ocean surface temperature has historically been estimated using linear regression and statistical approaches, such as the "Autoregressive Integrated Moving Average (ARIMA)" models [8], Machine learning techniques such as "support vector machines (SVMs)" have been employed in several types of research to predict SST [9] [10]. The "particle swarm optimization (PSO)" is also used for SST predictions in [11].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results revealed that the ARIMA model performs better forecasting linear time series, while [24,32], the remaining service life of aircraft engines prediction [31], and the P M 2 . 5 concentrations time series data set (a heterogeneous data set mixed one-dimension series data) [41], temperature [29]. The researchers also publish the combination methods that were used to forecast climate change by machine learning methods such as support vector regression, random forest, and K-nearest neighbors [36].…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, a few researchers predict COVID-19 pattern using ARIMA [8][9][10][11][12][13][14][15]. However, ARIMA model have a limitation where it's normally only can handle a linear time series data structure [16]. However, approximations by ARIMA models are inadequate in representing a barrier in time series forecasting for researchers particularly for nonlinear pattern [17].…”
Section: Introductionmentioning
confidence: 99%
“…The SVMs, which were first introduced by Vladimir Vapnik in 1995 [19] in the domain of statistical learning theory and structural risk minimization, have been shown to operate well on a variety of forecasting and classification issues. The SVMs could also cope with or address difficulties like nonlinearity, local minimum, and high dimension in which ARIMA model [16,[20][21][22]. SVMs models have recently been used to handle issues such as nonlinear, local minimum, and high dimension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation